The Comparison of Vertical Ground Reaction Force during Forward and Backward Walking among Professional Male Karatekas with Genu Varum and Normal Knees - Heydar Sadeghi; Siavash Shirvanipour; Raghad Mimar (Biyumikānīk-i varzishī)
Objective: The purpose of this study was to compare vertical ground reaction force during forward and backward walking among the male professional Karatekas with genu varum and normal knee. Methods: 20 professional male Karates (in genu varum and normal groups) participated in this semi-experimental study. The vertical ground reaction force was measured using force plate system during forward and backward walking utilizing 250 Hz frequency. Mixed ANOVA test was run to analyze the obtained data. Results: The first force peak was significantly higher during backward walking (p=0.00) than forward walking (p=0.03). The second force peak was significantly lower in non-dominant limb during backward walking than forward walking (p=0.01). The first force peak in dominant limb during backward walking and in non-dominant limb during forward walking were significantly higher in normal group [(p=0.00), (p=0.06)]. Also, depth force during forward walking was significantly more in the normal group ((p=0.01), (p=0.01)). While, the second force peak in dominant limb during backward-forward-walking was significantly more in genu varum group [(p=0.04), (p=0.05)]. Conclusion: Based on the results of present study, genu varum can be considered as an effective factor on vertical ground reaction force (as predictor factor of musculoskeletal injuries among the Karate professionals, and backward walking can cause a change in vertical ground reaction force more than forward walking does.